Cognitive behavioral therapy to improve emotion regulation skills in cyberbullying perpetrators among students - Gajah, Nurlaila Sahfitri; Rusmana, Nandang; Saripah, Ipah (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study aims to explore the effectiveness of cognitive behavioral therapy in improving emotion regulation among students of cyberbullying perpetrators and its application in guidance and counseling services. The research method used was descriptive qualitative with a literature review/study design. Data collection was conducted through references from books and journals relevant to the study, specifically those related to enhancing emotion regulation among perpetrator students of cyberbullying through counseling service interventions using a cognitive behavioral therapy. Data analysis was carried out by connecting, comparing, presenting, and finally concluding the findings from supporting reference materials. The study results indicate that cognitive behavioral therapy is effective in improving emotion regulation skills through restructuring negative thought patterns, self-awareness training, and reinforcing adaptive responses. The implementation of cognitive behavioral therapy in counseling services, both individually and in groups, can serve as a preventive and curative strategy to reduce aggressive online behavior. This study is expected to serve as a reference for school counselors in designing appropriate interventions for perpetrator students of cyberbullying.